THE MEDIATING ROLES OF SATISFACTION AND LOYALTY CARD PROGRAM ON THE RELATIONSHIP BETWEEN CUSTOMER PERCEIVED VALUE AND BRAND LOYALTY - Secioria, Rae (Journal of Business And Entrepreneurship, 2019)
Loyalty card programs have been utilized by marketers to improve the consumers’ recurring buying behavior by increasing the company’s value proposition. It is essential to observe and examine the customers’ perceived value towards brand loyalty and customer profitability. Therefore, this research measured the relationship between customer’s perceived value towards satisfaction and loyalty card program and those mediating factors towards brand loyalty and profitability. The structural equation modelling technique (AMOS) was used to evaluate the research model, and the results revealed that loyalty card programs serve as the strongest factor that affects the relationship between customers’ perceived value and brand loyalty. Keywords: customer perceived value, satisfaction, loyalty card program, brand loyalty, customer profitability Program kartu loyalitas telah digunakan oleh pemasar untuk meningkatkan perilaku pembelian berulang konsumen dengan meningkatkan proposisi nilai perusahaan. Sangat penting untuk mengamati dan menguji nilai yang dirasakan pelanggan terhadap loyalitas merek dan profitabilitas pelanggan. Oleh karena itu, penelitian ini mengukur hubungan antara persepsi nilai pelanggan terhadap program kartu kepuasan dan loyalitas dan faktor-faktor penengah terhadap loyalitas dan profitabilitas merek. Teknik pemodelan persamaan struktural (AMOS) digunakan untuk mengevaluasi model penelitian, dan hasilnya mengungkapkan bahwa program kartu loyalitas berfungsi sebagai faktor terkuat yang mempengaruhi hubungan antara persepsi nilai pelanggan dan loyalitas merek. Kata Kunci: nilai yang dirasakan pelanggan, kepuasan, program kartu loyalitas, loyalitas merek, profitabilitas pelanggan